2013
DOI: 10.1002/jsfa.6456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction solvents and plant parts used on the antihyperlipidemic and antioxidant effects ofGarcinia atroviridis: a comparative study

Abstract: Aqueous and methanol extracts of G. atroviridis showed higher antihyperlipidemic and antioxidant effects, respectively. Total phenolic and flavonoid contents showed significant correlations with antioxidant but not with antihyperlipidemic activities, indicating the involvement of other compounds. Contrary to the traditional belief, the present findings suggest that the fruit has higher antihyperlipidemic potential than the fruit rind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…The reducing power of Gsp was determined using the ferric reducing ability of plasma assay (Almansoub, Asmawi, & Murugaiyah, ). A standard curve was prepared using different concentrations (10–100 mmol/L) of FeSO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reducing power of Gsp was determined using the ferric reducing ability of plasma assay (Almansoub, Asmawi, & Murugaiyah, ). A standard curve was prepared using different concentrations (10–100 mmol/L) of FeSO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…The reducing power of Gsp was determined using the ferric reducing ability of plasma assay (Almansoub, Asmawi, & Murugaiyah, 2014).…”
Section: Reducing Power Assaymentioning
confidence: 99%
“…other study compares different plant part and extraction process in antihyperlipidemic activity in poloxamer 407-induced hyperlipid rat. It was found that aqueous extract of ripe fruit exhibit antihyperlipidaemic activity where total cholesterol and triglyceride was lowered at 34 hours (20). To sum up, the findings indicated and agreed that fruit extract of G.…”
Section: Antihyperlipidemic/antihyperclolesteromic/antiobesity Activimentioning
confidence: 53%
“…other conclusion also include that leaves are better in antioxidant activity compared to stem part. Although such remarks made by previous author, interesting finding by Al-Mansoub et al (20) stated that stem extract also have better antioxidant activity compared to leaves and fruit when extracted using methanol. Leaves part however, show better antioxidant capacity when extracted using water.…”
Section: Antioxidant Activitymentioning
confidence: 82%
“…Belinjau / Melinjau Seeds are prepared as crackers, in cooking dishes (soup) and as coffee substitute Bhat and Yahya, 2014;Voon and Kueh, 1999 Mirfat et al Phytochemistry and biological properties of underutilised fruits -Mansoub et al, 2014;Gerten et al, 2015;Salma et al, 2006 Garcinia dulcis…”
Section: Gnetum Gnemonmentioning
confidence: 99%